Beta‐2‐Glycoprotein‐I Deficiency Could Precipitate an Antiphospholipid Syndrome‐like Prothrombotic Situation in Patients With Coronavirus Disease 2019. Issue 4 (19th March 2021) - Serrano, Manuel; Espinosa, Gerard; Lalueza, Antonio; Bravo‐Gallego, Luz Yadira; Diaz‐Simón, Raquel; Garcinuño, Sara; Gil‐Etayo, Javier; Moises, Jorge; Naranjo, Laura; Prieto‐González, Sergio; Ruiz‐Ortiz, Estibaliz; Sánchez, Beatriz; et al.
Abstract : Objective: Patients with coronavirus disease 2019 (COVID‐19) present coagulation abnormalities and thromboembolic events that resemble antiphospholipid syndrome (APS). This work has aimed to study the prevalence of APS‐related antigens, antibodies, and immune complexes in patients with COVID‐19 and their association with clinical events. Methods: A prospective study was conducted on 474 adults with severe acute respiratory syndrome coronavirus 2 infection hospitalized in two Spanish university hospitals. Patients were evaluated for classic and extra‐criteria antiphospholipid antibodies (aPLs), immunoglobulin G (IgG)/immunoglobulin M (IgM) anticardiolipin, IgG/IgM/immunoglobulin A (IgA) anti‐β2‐glicoprotein‐I (aβ2GPI), IgG/IgM antiphosphatidylserine/prothrombin (aPS/PT), the immune complex of IgA aβ2GPI (IgA‐aβ2GPI), bounded to β2‐glicoprotein‐1 (β2GPI) and β2GPI levels soon after COVID‐19 diagnosis and were followed‐up until medical discharge or death. Results: Prevalence of aPLs in patients with COVID‐19 was as follows: classic aPLs, 5.8%; aPS/PT, 4.6%; IgA‐aβ2GPI, 15%; and any aPL, 21%. When patients were compared with individuals of a control group of a similar age, the only significant difference found was the higher prevalence of IgA‐aβ2GPI (odds ratio: 2.31; 95% confidence interval: 1.16‐4.09). No significant differences were observed in survival, thrombosis, or ventilatory failure in aPL‐positive versus aPL‐negative patients. β2GPI median levels were much lower in patients with COVID‐19 (15.9 mg/l) than in blood donors (168.8 mg/l; P < 0.001). Only 3.5% of patients with COVID‐19 had normal levels of β2GPI (>85 mg/l). Low levels of β2GPI were significantly associated with ventilatory failure ( P = 0.026). Conclusion: β2GPI levels were much lower in patients with COVID‐19 than in healthy people. Low β2GPI‐levels were associated with ventilatory failure. No differences were observed in the COVID‐19 evolution between aPL‐positive and aPL‐negative patients. Functional β2GPI deficiency could trigger a clinical process similar to that seen in APS but in the absence of aPLs.